Clinical, histopathological characteristics and immunohistochemical findings in lichen planus pigmentosus - Ramesh M Bhat; Teena Ramesh Mathanda; C S Jayaprakash; Sukumar Dandakeri (Wolters Kluwer Medknow Publications, 2017)
Background: Lichen planus pigmentosus (LPP), a rare variant of lichen planus, is reported in various ethnic groups, more often from the Indian subcontinent and the Middle East. Aims: Although the condition is encountered quite often by dermatologists of this region, the data on the clinical, pathological, and immunohistochemical (IHC) aspects of LPP are limited. This prospective study is aimed towards filling this lacuna. Materials and Methods: Data were collected from thirty clinically diagnosed cases of LPP who presented to the dermatology outpatient department. Skin biopsy and blood investigations were conducted and the specimens were further analyzed for their histopathological features and IHC staining for CD4+, CD8+ T-lymphocyte subsets along with CD45RO (UCHL-1), and CD68. The results were statistically analyzed. Results: The study showed a female preponderance (56.7%). Photo aggravation as a precipitating cause was seen in 40% of the individuals. The lesions with duration <4 months had a more intense inflammatory infiltrate on histology. CD4+ and CD8+ cells showed very good Pearsons correlation on statistical analysis. CD45 was seen in association with CD8+, and staining for CD68 to assess the macrophage density showed a close correlation with CD45RO. Limitations: Small sample size. Conclusion: LPP represents a misguided lesional immune response pattern. The intense inflammatory infiltrate seen in the early lesions necessitates prompt treatment to arrest progression which may prevent the chronic pigmentary phase of the disease.